Assessment of the effects of decontamination and storage methods on the structural integrity of human enamel - Adriana Rodrigues de FREITAS; Fábio Duarte da Costa AZNAR; André Luís da SILVA; Arsenio SALES-PERES; Silvia Helena de Carvalho SALES-PERES
Abstract Introduction The storage of teeth for use in research is a controversial issue with no consensus on the most appropriate treatment method for this purpose. Objective The aim of this study was analyze the effectiveness and the influence of different methods of decontamination and storage of human enamel samples, in order to maintain their integrity. Material and method The sample consisted of 124 molars distributed randomly into three groups according to the method: control - distilled water, 0.1% thymol and 0.02% sodium azide. The tests performed were laser fluorescence, surface microhardness and profilometry analysis (0, 15 and 30 days) and Microbiological test (7, 15 and 30 days). Data were analyzed by the ANOVA and Tukey tests (P <0.05). Result In the laser fluorescence test, thymol proved to be more feasible for maintaining the integrity of the dental organ, since it did not show significant variations in values among the analyzed periods (P> 0.05). The surface microhardness analysis showed loss of tooth structure in all methods, and sodium azide led to a lower level of tooth loss. Profilometry analysis showed loss of mass in all groups whereas sodium azide showed the greatest loss. None of the methods was able to inhibit bacterial growth. Conclusion Among the processing methods analyzed none was able to combine effective decontamination and storage with maintenance of the structural integrity of the human enamel.